Hereditary stable tubes in module categories - Simson, D.; Skowronski, A. (Algebra and Discrete Mathematics, 2007)
The concepts of a self-hereditary stable tube T and a hereditary stable tube T in a module category modA are introduced, where A is a finite dimensional algebra over an algebraically closed field. Characterisations of self-hereditary stable tubes and hereditary stable tubes are given, and illustrative examples of such tubes are presented. Some open problems are presented.